2012
DOI: 10.1002/jbt.21439
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Endocrine Disrupting Effects of the Flame Retardant Mixture Firemaster® 550 in Rats: An Exploratory Assessment

Abstract: Firemaster® 550 (FM 550), a fire-retardant mixture used in foam-based products, was recently identified as a common contaminant in household dust. The chemical structures of its principle components suggest they have endocrine disrupting activity, but nothing is known about their physiological effects at environmentally relevant exposure levels. The goal of this exploratory study was to evaluate accumulation, metabolism and endocrine disrupting effects of FM 550 in rats exposed to 100 or 1000 μg/day across ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
236
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(248 citation statements)
references
References 49 publications
10
236
2
Order By: Relevance
“…Bearr et al (2012) detected EH-TBB in tissues from fathead minnows (Pimephales promelas) 22 days after cessation of FM550 exposure. SD rat dams administered FM550 (1 mg/day) during pregnancy and nursing were observed to have increased serum thyroxine and decreased hepatic esterase activity (Patisaul et al, 2013). Furthermore, in these studies, female pups displayed high anxiety phenotypes whereas male offspring had significantly impaired glucose tolerance.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Bearr et al (2012) detected EH-TBB in tissues from fathead minnows (Pimephales promelas) 22 days after cessation of FM550 exposure. SD rat dams administered FM550 (1 mg/day) during pregnancy and nursing were observed to have increased serum thyroxine and decreased hepatic esterase activity (Patisaul et al, 2013). Furthermore, in these studies, female pups displayed high anxiety phenotypes whereas male offspring had significantly impaired glucose tolerance.…”
mentioning
confidence: 72%
“…Finally, an exploratory assessment of possible species-or sexrelated differences in the disposition of EH-TBB was performed using male B6C3F1/Tac mice in a prior paradigm (Buchanan et al, 1997). The dose range tested herein was based on highrange human exposures to EH-TBB in household dust, as described by Patisaul et al (2013).…”
mentioning
confidence: 99%
“…The results indicate that the 1.0 mg L -1 dose of FM-550 caused significant malformations in larval zebrafish compared to adolescent zebrafish (Bailey and Levin, 2015). In an in vivo study by Patisaul et al (2013), elevated body weight at a high-dose exposure (1,000 µg day -1 ) was the most significant developmental effect of FM-550 in Wistar rats. This effect became evident prior to adolescence and continued into adulthood for both sexes.…”
Section: Developmental Toxicitymentioning
confidence: 83%
“…Studies of acute toxicity in Wistar rats showed that a single dose of 5,000 mg kg -1 FM-550 did not produce lethality, outwardly observable effects, or gross changes at necropsy after 15 days (USEPA, 2015). Experimental data also showed that it was possible for BEH-TEBP to be absorbed after oral exposure with a commercial mixture FM-550 (Patisaul et al, 2013). BEH-TEBP was found in the tissues of pregnant Wistar rats after exposure to the commercial mixture; however, BEH-TEBP was not found in the offspring even though exposure had occurred from gestation to lactation (Patisaul et al, 2013).…”
Section: Acute Toxicitymentioning
confidence: 92%
See 1 more Smart Citation